Risk Factors Associated With Sustaining a Sport-related Concussion: An Initial Synthesis Study of 12, 320 Student-Athletes. (17th February 2018) - Brett, Benjamin L; Kuhn, Andrew W; Yengo-Kahn, Aaron M; Solomon, Gary S; Zuckerman, Scott L
Abstract: Objective: The empirical identification of risk factors associated with sport-related concussion (SRC) may improve the management of student-athletes. The current study attempted to identify and quantify bio-cognitive risk factors associated with sustaining a SRC. Methods: Cross-sectional ambispective study; level of evidence, 3. Neurocognitive testing of 12, 320 middle school, high school and collegiate athletes was completed at preseason baseline and post-SRC. Univariate and multivariable logistic regressions were used to determine which pre-injury variables accurately predicted the occurrence of SRC. A quantitative risk score for each variable was developed. Results: Five of 13 variables maintained significance in the multivariable model with the associated weighted point scores: SRC history (21), prior headache treatment (6), contact sport (5), youth level of play (7), and history of ADHD/LD (2). Six stratified groups were formed based on probability of SRC, which produced an area under the curve (AUC) of 0.71 (95% CI 0.69–0.72, p < .001). Though the model was a significant predictor of SRC ( X 2 = 1, 112.75, p < .001), the effect size was small and accounted for only 16% of the overall variance. Conclusions: An initial aggregate model of weighted bio-cognitive factors associated with increased odds of sustaining a SRC was developed. Previously validated factors were confirmed, yet a large source of variance remained unexplained. These findings emphasize the need to expand the host factors studied when assessing SRC risk, and that the existing, empirically based bio-cognitive factors do not adequately quantify the risk of SRC.